Parting with "blue monday": Preferences in home production and consumer responses to innovations - Ulrich Witt; Julia Sophie Woersdorfer (Max Planck Institute of Economics, 2011)
How can economic theory explain the reasons why consumers adopt innovations? Using the example of innovations in washing machines two approaches are compared. The first focuses in the manner of household production theory on changes in constraints without specifying preferences, leading to the well-known time substitution hypothesis. The second approach develops specific hypotheses about consumer preferences and focuses on how technical change accounts for them. The two approaches are empirically evaluated with a data set representing the motives suggested in washer advertisements for purchasing new vintages of machines over the period 1888 to 1989 in the US.
Keywords: A12; D01; D11; D12; D13; N3; 330; home production; preferences; consumer motivation; product innovation; innovation diffusion; time substitution hypothesis; direct utility; Konsumentenverhalten; Innovationsdiffusion; Haushaltsproduktion; Zeitverwendung; Präferenztheorie; Waschmaschine; Schätzung; USA